Current use of Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA) in trauma☆. (December 2017) - Ordoñez, Carlos A.; Manzano‐Nunez, Ramiro; del Valle, Ana Milena; Rodriguez, Fernando; Burbano, Paola; Naranjo, Maria Paula; Parra, Michael W.; Ferrada, Paula; Solís‐Velasco, Mónica Alejandra; García, Alberto F.
ABSTRACT : Introduction: : Non‐compressible torso haemorrhage is the leading cause of death in trauma cases. This has led to the development of new devices to control bleeding, including Resuscitative Endovascular Balloon Occlusion of the Aorta (REBOA). Objective: : To perform a non‐systematic review of the literature on the use of Resuscitative Endovascular Balloon Occlusion of the Aorta in trauma. Materials and methods: : A systematic literature search through Medline was conducted. Articles relevant to our objective were selected. A qualitative and narrative synthesis of results is presented. Results: : Our qualitative and narrative results show that Resuscitative Endovascular Balloon Occlusion of the Aorta could be a safe and effective intervention for the control of haemorrhage in abdomino‐pelvic trauma. Its use is controversial in thoracic trauma. Finally, the performance of this intervention may cause complications. Conclusion: : Resuscitative Endovascular Balloon Occlusion of the Aorta is an alternative that can be used in damage control surgery. It could be effective for early control of bleeding in patients with non‐compressible torso haemorrhage. As a complex intervention, REBOA is in its development phase, and the evidence available preclude us from providing strong recommendations. Uso actual del Balón de Resuscitación Aórtico Endovascular (REBOA) en trauma: RESUMEN: Introducción: : La hemorragia no compresible del torso es la principal causa de muerte asociada al trauma. Esto ha llevado al desarrollo de nuevos dispositivos para el control hemorrágico, uno de estos es el balón de resucitación aórtico endovascular. Objetivo: : El objetivo de este trabajo fue realizar una revisión no sistemática de la literatura con respecto al uso del REBOA en trauma. Materiales y métodos: : Se realizó una búsqueda sistemática de la literatura en MEDLINE, se seleccionaron los artículos relevantes para el logro de nuestro objetivo y con estos se realizó una síntesis cualitativa y narrativa de la literatura disponible. Resultados: : Nuestra síntesis cualitativa y narrativa muestra que el balón de resucitación aórtico endovascular podría ser una intervención segura y efectiva para el control de la hemorragia en trauma abdomino‐pélvico. Su uso es controvertido en trauma torácico. Finalmente, el uso del balón de resucitación aórtico endovascular puede causar complicaciones relacionadas con su aplicación. Conclusión: : El balón de resucitación aórtico endovascular (REBOA) es una alternativa en la cirugía de control de daños que podría ser efectiva en el control de la hemorragia no compresible del torso de origen abdomino‐pélvico. Al ser una intervención compleja, REBOA se encuentra todavía en fase de desarrollo y la evidencia disponible no es suficiente para proveer recomendaciones fuertes.